Foreign policy options for CARICOM : an analytical review - Vasciannie, Stephen (Jamaica, Ian Randle Publishers, 2006)
Looks at different elements that influence foreign policy formulation in CARICOM states as a group. Examines certain pervailing viewpoints amd policy options in respect of a particular subset of issues viz. trade and investment; human rights concerns; law of the sea; illegal drug exportation and transshipment; immigration matters; development assistance, and; security concerns.
Published for the UWI-CARICOM Project
Keywords: Foreign Policy; Foreign Relations; Caribbean Community; CARICOM